2011
DOI: 10.2174/1874922401104010054
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Violent Victimization to the Police: A Focus on Black, White, Asian and Hispanic Adolescent Victims

Abstract: Explorations of patterns of why and when citizens report crime to police are an important area of study in the field of criminology and criminal justice. Initial National Crime Survey data suggest that a substantial proportion of crime went unreported to the authorities (i.e., law enforcement reports as reflected by the Uniform Crime Reports). The purpose of this study is to enhance our understanding about reporting violence against adolescents to the police. This research examines the extent and nature of rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…Conversely, the results of Xie, Pogarsky, Lynch, and McDowall’s (2006) study of police notification decisions involving personal or household victimization suggested that White victims were more likely than other victims to notify the police, but only for household crimes. Similar crime-dependent race effects have also been reported in other studies, highlighting the need for research examining decisions by victims of specific crimes such as identity theft (e.g., Akers & Kaukinen, 2009; Felson et al, 1999; Fisher et al, 2003; Rennison et al, 2011).…”
Section: Reporting Victimization To Law Enforcementsupporting
confidence: 74%
“…Conversely, the results of Xie, Pogarsky, Lynch, and McDowall’s (2006) study of police notification decisions involving personal or household victimization suggested that White victims were more likely than other victims to notify the police, but only for household crimes. Similar crime-dependent race effects have also been reported in other studies, highlighting the need for research examining decisions by victims of specific crimes such as identity theft (e.g., Akers & Kaukinen, 2009; Felson et al, 1999; Fisher et al, 2003; Rennison et al, 2011).…”
Section: Reporting Victimization To Law Enforcementsupporting
confidence: 74%
“…Using data from the Women's Experience of Violence Study, Kruttschnitt and Carbone-Lopez (2009) reported that respondent race was significantly different among female crime victims who called the police and those who did not. For the most part, scholarship exploring the influence of race on reporting has centered on adolescent comparisons (see for e.g., Rennison et al, 2011) or a single race or ethnicity (Rennison, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research suggests that understanding why crime is not reported to the police is important for several reasons (Rennison, Gover, Bosick, & Dodge, 2011). Nonreporting undermines the capacity of the criminal justice system to perform its key functions.…”
Section: Introductionmentioning
confidence: 99%
“…Reporting violence against Hispanics to the police differs from other race/Hispanic origin groups as well. While the overall rate at which violence against Hispanics is similar for the overall population (Truman, 2011), the predictors of reporting violence against Hispanic victims differs from groups (Rennison et al, in press). Findings indicate that gender, type of violence, and weapon presence are not significant predictors of police reporting for Hispanic juvenile victims though these are considered some primary significant predictors of reporting from other juveniles as well as the population in general.…”
Section: Introductionmentioning
confidence: 99%